Genetic Testing for Autism Spectrum Disorder is Lacking Evidence of Cost-effectiveness - Ziegler, Andreas; Rudolph-Rothfeld, Wolfgang; Vonthein, Reinhard (Methods of Information in Medicine, 2017)
Background: Autism Spectrum Disorder (ASD) is a highly heritable neural development disorder characterized by social impairment. The earlier the diagnosis is made, the higher are the chances of obtaining relief of symptoms. A very early diagnosis uses molecular genetic tests, which are also offered commercially.Objective: Systematic review of the economic impact of genetic tests in ASD.Methods: We performed a systematic search of databases Pubmed, Medline, Cochrane, Econlit and the NHS Center for Reviews and Dissemination for articles in English and German from January 1, 2000 to December 31, 2015. Original articles published in peer- reviewed journals were screened in a two- step process. First, we focused our search on economic evaluations of genetic tests for ASD. Second, we searched for any economic evaluation (EE) of genetic tests.Results: We identified 185 EE of genetic tests for various diseases. However, not a single EE of genetic tests has been found for ASD. The outcomes used in the EE of the genetic tests were heterogeneous, and results were generally not comparable.Conclusion: There is no evidence for cost-effectiveness of any genetic diagnostic test for ASD, although such genetic tests are available commercially. Cost-effectiveness analyses for genetic diagnostic tests for ASD are urgently required. There is a clear lack in research for EE of genetic tests.
Keywords: Autism; ASD; genetic test; cost-effectiveness; JEL Classification I11